Lipid Production of Marine Green Microalgae Chlorella protothecoides BUUC1601 by Using Spent Coffee Grounds Hydrolysate - Hiransuchalert, Rachanimuk; Siranonthana, Nisa; Chedtaisong, Nuttapon; Setthamongkol, Pakawan; Yuyen, Yutthaya; Watanachote, Janjarus; Tapaneeyaworawong, Paveena; Rungsawang, Nongnuch; Kutako, Maliwan (Journal of Food Health and Bioenvironmental Science, 2023)
Spent coffee grounds are an organic waste that can be used as a source of microbial organic carbon. In this research, coffee grounds were hydrolyzed into a solution called spent coffee grounds hydrolysate (SCGH) using concentrated sulfuric acid. Then, the marine green microalgae, C. protothecoides BUUC1601, was cultured using SCGH. Growth performance and lipid accumulation of the microalgae were evaluated. The microalgae were cultured using a standard F/2 medium without and with SCGH added in the range of 2.5-15% of culture media (v/v). It was found that the microalgae had similar growth performance and biomass yield, i.e., the specific growth rate was in the range of 0.87-1.12 day-1 and the biomass yield was in the range of 0.05-0.08 g DW/L/day. Microalgae cultivation using F/2 with SCGH had an effect on lipid accumulation. It was found that using SCGH at 15% of the total volume resulted in an increase in the amount of lipid accumulation up to 66.03% of the dry weight. Of these, it was 2.89 times higher than the lipid content of microalgae cultured with no SCGH added. The content of monounsaturated fatty acids ranged from 46.15% to 46.53% and polyunsaturated fatty acids ranged from 32.40% to 34.62% of the total fatty acid content. Oleic acid (C18:1n9), an omega-9 fatty acid, was found to be the most abundant, accounting for over 30% of the total fatty acid content. In contrast, the omega-6 fatty acids linoleic acid (C18:2n6) and gamma-linolenic acid (C18:3n6) were found to be lower, accounting for 25.99%-27.20% and 6.03%-7.01% of the total fatty acid content, respectively. The omega-3 fatty acid such as alpha-linolenic acid (C18:3n3) was found at 4.20% in microalgae cultured using standard F/2 medium without SCGH, which was higher than in microalgae cultured with the addition of SCGH. Therefore, the addition of SCGH at a concentration of 2.5%-15% (v/v) can be used to cultivate C. protothecoides BUUC1601 for the lipid production with high unsaturated fatty acid content, which has the potential to be used in both aquaculture and functional food supplementation.